Studying the Opinions of the Population of Tashkent City on the Development of Alternative Energy Sources - Zayni Ugli, Urinov Murodjon (Journal of Innovation in Education and Social Research, 2024)
This article, considering the high global demand for alternative energy sources, presents the analytical results of a social survey conducted among specialists and consumers in Tashkent. The survey focuses on the process of installing and utilizing one of the alternative energy sources, namely solar panels.